MAP PROJECT METHODE PADA KELAS GEOGRAFI - Banowati, Eva (Lembaran Ilmu Kependidikan, 2008)
Research was carried out in the Settlement Geography Class, started on September 1 to September 22, 2008 (4 periods). The subject of the research was all 2007/2008 students, participants of the Settlement Geography Class (Population Research). The problem was that their quality in mapping and site plan projects was poor. The purpose of the research: students are able to do mapping and site plan projects individually, have expertise in mapping the patterns and distribution of settlements around them and other places, and able to communicate their project in the class discussion forum. The method used in this research was classroom action research model Kemmis Mc. Taggart; input, process and output variables. Qualitative data was gathered using questionnaires and observation. Indicator of the success is the increase in students’ understanding individually and in group. Comprehensive analysis is from the first cycle to the second cycle (the last). First cycle found that students did not do the projects seriously. Reflection of the first cycle, more focus on areas, showed an improvement although not a significant one. Each group was then analyzed and showed that the best group scored 7.33. The mapping and site plan projects carried out on the second cycle showed that students’ understanding and seriousness was higher. Third cycle was unnecessary to do as it took only 79.03 minutes for students to finish the project. The conclusion is that the Achievement Index will increase if students do the projects seriously. Map project method means as a variety of learning in the Settlement Geography Class. Kata Kunci: denah, Map project method , site plan